The Effect of Artificial Intelligence Implementation on Digital Governance Performance Mediated by Digital Infrastructure and Human Resource Competence - Dimas Andianto; Furqon Syarief Hidayatulloh; Amiruddin Saleh (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the role of Artificial Intelligence (AI), human resource (HR) competence, and digital infrastructure in supporting the performance of Digital Governance in Indonesia. The results indicate that HR competence and digital infrastructure have a significant direct influence on Digital Governance performance, with HR competence being the most dominant factor. Meanwhile, AI implementation does not have a significant direct effect but exerts an indirect impact through the mediation of HR competence and digital infrastructure. These findings emphasize the importance of a systemic approach to improving Digital Governance performance by optimizing AI utilization supported by competent human resources and reliable infrastructure. This study contributes both theoretically and practically to supporting digital transformation in the public sector and provides a basis for evidence-based policy formulation toward more effective, efficient, and sustainable governance.